2018
DOI: 10.1039/c8sm01591k
|View full text |Cite
|
Sign up to set email alerts
|

Percolation behaviors of model carbon black pastes

Abstract: The percolation behaviors of a series of high-structured carbon black (CB) pastes (CB weight fractions 10–25 wt%, ethyl cellulose as the binder, α-terpineol as the solvent) were systematically investigated using analyses of rheology and impedance spectra together with characterization via small-angle X-ray scattering (SAXS) and scanning electron microscopy (SEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…45 Adding the CB particles to the paraffin oil transformed the free-flowing liquid into a paste with a jammed structure that does not creep under its own weight as illustrated in Figure 1. Note that the time evolution of such CB-loaded pastes has been studied by Jiang et al, 46 The rheological response at larger strain, however, shows that the oil-material has a tendency to flow, in the sense that the loss modulus exceeds the storage modulus as a function of strain in oscillatory shear experiments, as exemplarily shown in Figure 2a for N234-filled oil. In polymer, the nanocomposite made with the same carbon black presents no indication of flow onset as seen in Figure 2b.…”
Section: Resultsmentioning
confidence: 81%
“…45 Adding the CB particles to the paraffin oil transformed the free-flowing liquid into a paste with a jammed structure that does not creep under its own weight as illustrated in Figure 1. Note that the time evolution of such CB-loaded pastes has been studied by Jiang et al, 46 The rheological response at larger strain, however, shows that the oil-material has a tendency to flow, in the sense that the loss modulus exceeds the storage modulus as a function of strain in oscillatory shear experiments, as exemplarily shown in Figure 2a for N234-filled oil. In polymer, the nanocomposite made with the same carbon black presents no indication of flow onset as seen in Figure 2b.…”
Section: Resultsmentioning
confidence: 81%
“…For example, shear-induced log-rolling structures aligned in the vorticity direction at low dimensionless shear rates have been observed with CB [22][23][24][25] . The structure of CB also shows shear history dependence, therefore, the suspensions can have a tunable yield stress 26 , elastic modulus 20 , conductivity 27 , and impedance 28 under different shear histories.…”
Section: Introductionmentioning
confidence: 99%
“…A notable feature of the AP hydrocolloids in this study is the applicability of concentration superposition (TCS), as shown in Figure 4. This feature was first rep for suspensions composed of weakly attractive carbon blacks [43], and a recent int tation further attributed the underlying physics to the "colloidal meshes" formed both dilute (dispersed) and concentrated(interconnected) conditions [44]. It thus ap that AP hydrocolloids may have fostered similar (weakly attractive) colloidal spec the range of concentrations investigated.…”
Section: Time-concentration Superposition Of Ap Hydrocolloidsmentioning
confidence: 77%
“…Although more work is clearly required to resolve the underlying structural features, it seems that AP hydrocolloids share viscoelastic features of both entangled polymer solution and colloidal suspension, making their true attributes highly intriguing. The referred case of weakly attractive carbon black pastes [44] present a somehow likely TCS, however, with the dynamic modulus data over a frequency range of 12 orders of magnitude. The material natures of pectin and carbon blacks are apparently different; yet it is generally believed that soft matter physics principles could alternatively be used to address important problems in the food industry.…”
Section: Time-concentration Superposition Of Ap Hydrocolloidsmentioning
confidence: 77%